Evaluating green city development in China using an integrated analytical toolbox. (10th May 2023) - Huang, Wei; Gao, Bing; Cui, Shenghui; Huang, Yunfeng; Zhang, Xiangtong; Shen, Yusheng; Fang, Xuejuan; Wang, Lan; Xu, Su; Zuo, Shudi
Abstract: Promoting green city development has become a core measure to deliver eco-civilization in China, and China's practice in this regard could provide an insightful reference for the sustainable transformation of cities in other countries. However, multi-city empirical research on green city assessment in China has so far been limited, leaving plenty of room for improvement in the understanding of the issues regarding (1) characterization of disparities in the green development status among cities; (2) identification of key factors leading to the disparities; and (3) exploration of potential approaches to promoting green city development. This study integrates comprehensive index analysis, coordination analysis, difference analysis, and correlation analysis into an analytical toolbox, and investigates the green development of 36 major cities in China in 2015. The overall performance of these cities was not high, and showed clear regional imbalance. Relatively small cities, and the green transformation of consumption, deserve more concern in the near future. Other than a conventional comprehensive index, coordination degree brings a novel perspective to understand the green development status of cities. The key indicators contributing to the performance difference among the cities were generally related to sustainable lifestyles and decoupling consumption from resources and environmental pressures. In the end, increase of economic development quality, stimulation of social innovation, improvement of urban infrastructure, and appropriate urban density are proposed as policy suggestions to facilitate cities' green transition. Graphical abstract: Image 1